Studi Kelayakan E-Modul Interaktif Canva Bermuatan Realistic Mathematics Education untuk Materi Bangun Datar di Madrasah Ibtidaiyah - Cahya Amalia Chusna; Maftukah, Fajriyani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2025)
This study aims to assess the feasibility of an interactive e-module developed using Canva, incorporating the Realistic Mathematics Education (RME) approach, for the topic of plane figures in first-grade Madrasah Ibtidaiyah. The research employed a development method using the ADDIE model, with a focus on the evaluation stage. The feasibility assessment involved three expert validators—namely a subject matter expert, a media expert, and a mathematics teaching practitioner—and was followed by limited-scale user testing involving students in three stages: individual trials (3 students), small group trials (8 students), and field trials (16 students). Data were collected using validation sheets and practicality questionnaires based on a four-point Likert scale, and analyzed descriptively both quantitatively and qualitatively. The results showed that the e-module achieved a feasibility score of 85.4% from the subject matter expert, 95.4% from the media expert, and 92.7% from the practitioner, all categorized as “very feasible.” Student trials also yielded highly positive results, with individual trials reaching 100%, small group trials 87.5%, and field trials 95% in terms of practicality and acceptance. Based on these findings, the developed e-module is considered highly feasible for use in mathematics learning, particularly for teaching plane figures at the Madrasah Ibtidaiyah level. The module effectively supports engaging, interactive, and contextual learning experiences aligned with the characteristics of early grade learners